2018
DOI: 10.15640/jthm.v6n1a5
|View full text |Cite
|
Sign up to set email alerts
|

A Tourism and Hospitality Education Management Model: The Case of the Tourism Department of Sultan Qaboos University

Abstract: The tourism and hospitality education is a branch of the overall tourism and hospitality industry that is dedicated to providing the industry with well educated, adequately trained, and committed workforce. The Tourism Department at the College of Arts and Social Sciences (Sultan Qaboos University), Oman, has been providing the Omani society with undergraduate tourism and hospitality educational services since Fall 2001. Even though Tourism Department graduates are not facing any employment concerns, fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Over the last 10 years two instructors were responsible for teaching those courses, their comments tackled three main issues: Several studies by field specialists (Al-Balushi 2008, UNWTO andMOT 2011) indicated that Omani hospitality discipline graduates do not work in the field, especially, they stand-away of working in food production or service. Tourism Department graduates' enrolment in the industry workforce is so limited, they mainly choose the government (public) sector (Atef 2018). Job opportunities in indirectly related fields is the reason that the Hospitality Management Specialization is still surviving, in many cases, employers do not differentiate between specializations, for them they are all -Tourism Department Graduates‖.…”
Section: Part C: Courses Instructors Feedbackmentioning
confidence: 99%
“…Over the last 10 years two instructors were responsible for teaching those courses, their comments tackled three main issues: Several studies by field specialists (Al-Balushi 2008, UNWTO andMOT 2011) indicated that Omani hospitality discipline graduates do not work in the field, especially, they stand-away of working in food production or service. Tourism Department graduates' enrolment in the industry workforce is so limited, they mainly choose the government (public) sector (Atef 2018). Job opportunities in indirectly related fields is the reason that the Hospitality Management Specialization is still surviving, in many cases, employers do not differentiate between specializations, for them they are all -Tourism Department Graduates‖.…”
Section: Part C: Courses Instructors Feedbackmentioning
confidence: 99%
“…A comprehensive study of the tourism undergraduate study plan (2010) indicated that the 12 "Specialization Requirements" courses (See Table 1) based on the courses files analysis could be classified as "Operational" and/or "Managerial" courses (Atef, 2018)…”
Section: Structure Of the Tourism Undergraduate Program (Study Plan 2...mentioning
confidence: 99%
“…Tourism education is how a tourism authority prepares human resources to work professionally in the development of tourism sectors (Malihah & Setiyorini, 2014, October). It is a significant part of the entire tourism industry and is also devoted to providing a welleducated, dedicated, and appropriately trained workforce in the tourism industry (Atef, 2018). It is known that management education has taught people to plan, organize, execute, manage and evaluate any task effectively and efficiently.…”
Section: Definition Of Tourism and Hospitality Management (Thm) Educa...mentioning
confidence: 99%